Strengthening human resources for health through multisectoral approaches and leadership: the case of Cameroon - S Kingue; E Rosskam; AC Bela; A Adjidja; L Codjia
Problem Cameroon has a severe shortage of human resources for health (HRH) and those that are available are concentrated in urban areas. Approach As the result of a national emergency plan for the years 2006-2008, innovative strategies and a multisectoral partnership - led by the Ministry of Public Health and supported by diverse national and international organizations - were developed to address the shortages and maldistribution of HRH in Cameroon. Local setting At the time that the emergency plan was developed, Cameroon had health services of poor quality, an imbalance between HRH training and employment, a maldistribution of HRH between urban and rural areas and a poor allocation of financial resources for HRH. It also lacked an accreditation system for use in the training of health workers. Relevant changes Between 2007 and 2009, the number of active health workers in Cameroon increased by 36%, several new institutions for higher education in health care and training schools for paramedical staff and midwives were opened, and a national strategy for universal health coverage was developed. Lessons learnt In the improvement of HRH, strong leadership is needed to ensure effective coordination and communication between the many different stakeholders. A national process of coordination and facilitation can produce a consensus-based view of the main HRH challenges. Once these challenges have been identified, the stakeholders can plan appropriate interventions that are coordinated, evidence-based and coherent.